Oxytocin reduces asymmetries in dominance relationships between pairs of captive female lions - Jessica C. Burkhart; Abby Guthmann; Evianne M. DuBois; Sarah R. Heilbronner; Craig Packer (Scientific Reports)
Abstract Free-ranging female African lions maintain symmetrical social relationships by respecting each other’s “ownership” of valuable food items rather than by supplanting subordinates according to well-defined dominance hierarchies. However, captivity often skews relationships in captive carnivores, hence we investigated whether captive female lions demonstrate obvious dominance relationships. Oxytocin has been shown to elicit context-specific impacts that equalize dominant subordinate relationships, thus we hypothesized that oxytocin would reduce any asymmetries found between dominants and subordinates in captive lions. We designed two experimental protocols for investigating pairwise relationships. We first identified dominant individuals by performing neutral trials that allowed each female equal opportunity to possess the food item. Second, we performed non-neutral trials that biased the opportunity for subordinates to gain possession (“ownership”) of the food and thereby determined whether dominants would still gain access to the resource. The neutral tests revealed that pairs of captive females do display dominance relationships, with one individual possessing the resource more than the other. However, in non-neutral trials, subordinates behaved less submissively by increasing aggression and their possession of the resource after receiving oxytocin compared to receiving saline solution. Our study not only reaffirms the social dynamics altered by captivity, but also highlights the potential for oxytocin to mitigate these disturbances.